Applied capabilities of geodatabases in the archiving and recording of archaeological data- Applied Study in the Archeological Areas of Al – Ula - - Abu Khalil, Wafaa Saleh Mohammed (Journal of natural sciences, life and applied sciences, 2018)
This study addresses a vital subject matter to specialists in archeology, which is the application of geographic information systems (GIS), as one of the most important spatial techniques that deal efficiently with archaeological data, information and records. Given that the traditional methods are still followed in many of the spatial sciences in Saudi Arabia, including archeology, especially in the processes of recording and archiving archaeological records and resources, it is, however, necessary to apply new technologies in this field. The operations of recording and archiving are important processes in the conservation and management of archaeological resources and study, but storage of archaeological data and records using traditional methods proved to be more difficult, as well as the possibility of loss or damage. As such, a lot of data processing and query tasks become difficult for researchers and those interested in archeology. Therefore, the idea of this study is to test the capabilities of geodatabases for cartographic records and archaeological data. For this purpose, defined the required data characteristics, followed by defining, setting up, and implementing the required standards. Finally, an evaluation step was performed to test performance and applicability of the geodatabase through experimenting with many functions related to data query and analysis tasks that might be needed by users and specialists in archeology. The main data used for testing were on some of the data and information for the archaeological areas of Al-Ula. The study showed that unlimited capabilities can be utilized for geodatabases, to facilitate the tasks of the specialists in the archaeological field. The study provided a number of recommendations; namely, adopting of GIS in the field of archeology in Saudi Arabia; applying geodatabase for Recording and archiving of archaeological data, and conducting future studies in the field of archaeological data conversion and coding from the perspective of GIS database concepts and procedures.